Prevalence of Anemia in Children-A Hospital-Based Study Conducted in Northern Kerala, India - Fabin, Mohammed; Jayakumar, Jayakrishnan; Shanker, Swathy (Archives of Advances in Biosciences, 2024)
Introduction: Anemia is defined as a reduced hemoglobin content leading to minimized oxygen carrying capacity of the cell. Children are commonly affected by anemia which causes impaired development and cognitive defects in them. Among all the causes, iron deficiency is one of the most important contributing factors to the development of anemia. The prevalence of anemia varies in different regions. This study aims to find the prevalence of anemia among children in an urban population of Kerala. Materials and Methods: This was a retrospective observational study involving 192 children. The children were diagnosed as anemic if hemoglobin value was less than 11g/dl for those younger than 5 years and less than 11.4g/dl in those aged 5-11 years. The children were further diagnosed with mild, moderate or severe anemia based on their hemoglobin levels. Data were retrieved from the hematology reports and tabulated in Microsoft Excel. Analyses were done using SPSS software version 16.0. Results: This study showed the prevalence of anemia to be 54.7%. The majority of anemic children (48.6% ) were mildly anemic while 34.3% were moderately anemic, with 17.1% being severely anemic. Conclusion: In spite of active policy implementation for elimination of anemia, the prevalence of anemia continues to be high indicating the need for active intervention with early detection and treatment of anemia as a routine procedure.